Construction of an optimal bonus plan with the piecewise-linear incentive function in the framework of multistage games with complete information - G. A. Belyankin; E. N. Suetina (Путеводитель предпринимателя, 2020)
In present article the problem of interaction between employer and employee is considered as a game with complete information. We study the function of motivation, which is similar to suchfunctions in the actual HR practice. The mathematical model of personnel motivation is proposed. One-step and two-steps bonus schemes are considered.